Expected genetic gain in milk production trait through progeny testing in Murrah buffalo herds - KUMAR, VIJAY; CHAKRAVARTY, A K; PATIL, C S; VALSALAN, JAMUNA; MAHAJAN, ATUL (The Indian Journal of Animal Sciences, 2014)
The information of Murrah buffalo bulls from 7 sets of progeny testing under Network Project on Murrah buffalo improvement and maintained at Central Institute for Research on Buffalo (CIRB), Hisar; National Dairy Research Institute (NDRI), Karnal; Guru Angad Dev Veterinary and Animal Sciences University (GADVASU), Ludhiana; and Choudhary Charan Singh Haryana Agricultural University (CCSHAU), Hisar were used to estimate genetic gain. The first lactation 305-days or less milk yield (FL305MY) records of 832 daughters of 95 bulls. In the term of percent expected annual genetic gain best result found in set 3 with 0.78%.